This is a collective work of fiction...: Representation and Similitude in Michel Foucault and the statement of the soap operas shown by TV Globo - Rocha, Tacia [UNESP]; Coito, Roselene de Fatima [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2023)
At the concept of representation used for Michel Foucault, the reality is composed for the repetition and the new creation of something by means of not the similarity with the real. Drawing on the theoretical and methodological framework of Foucauldian Discourse Studies, this research has as objective to ask the concept of representation studied for Foucault in Ceci n'est pas une pipe, from Belgian painter Rene Magritte (1898-1967), and analyzing as this is retaken by the TV Globo teledramaturgy by means of the statement that appears in the final credits. The results reveal that the game enters the images in movement and the tram functions as the suspended pipes and painted in the picture The treason of the images, that are ficcionals and whose discomfort of the citizen that observes the image is decided from the statement that discloses that the workmanship is ficcional.
Keywords: Representation; Fiction; Audiovisual; Real; Reality